1997
DOI: 10.1063/1.872091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toroidal viscosity with neoclassical theory

Abstract: Toroidal rotation profiles are measured with charge exchange spectroscopy for a plasma heated with tangential neutral beam injection ͑NBI͒ in the Compact Helical System ͑CHS͒ heliotron/torsatron device ͓Ida et al., Phys. Rev. Lett. 67, 58 ͑1991͔͒ to estimate the toroidal viscosity. The toroidal viscosity derived from the toroidal rotation velocity shows good agreement with the neoclassical toroidal viscosity plus the perpendicular viscosity ( Ќ ϭ2 m 2 /s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…[11][12][13][14] There is an effect of flow damping in helical plasmas even in the toroidal direction caused by non-axisymmetry in toroidal direction, which is called the "parallel viscosity" and has been experimentally confirmed in the compact helical system (CHS) for the first time. 11,15 Spontaneous flows driven by radial electric field and ion temperature gradient were also observed where the parallel viscosity is relatively large, 16,17 and they are qualitatively consistent with neoclassical prediction. Recently, a large offset toroidal flow was observed with ion internal transport barrier (ion ITB) formation in the large helical device (LHD) and correlates with ion temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] There is an effect of flow damping in helical plasmas even in the toroidal direction caused by non-axisymmetry in toroidal direction, which is called the "parallel viscosity" and has been experimentally confirmed in the compact helical system (CHS) for the first time. 11,15 Spontaneous flows driven by radial electric field and ion temperature gradient were also observed where the parallel viscosity is relatively large, 16,17 and they are qualitatively consistent with neoclassical prediction. Recently, a large offset toroidal flow was observed with ion internal transport barrier (ion ITB) formation in the large helical device (LHD) and correlates with ion temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the burst rate is inversely related to the Helium concentration, however, the values of ∆v avg are lower for the 21% and 53% He concentration discharges. One possibility for this is the additional viscosity/damping to the rotation in the presence of magnetic perturbation, which can introduce higher harmonic field ripple [45]. To investigate the role of this perturbation, the amplitude of the magnetic probe signals, filtered between 25-50kHz (to obtain the component with 30kHz and associated chirping features associated with m=4,n=1), averaged over times both with bursts and without bursts are shown in Fig (10c).…”
Section: E Ion Species Dependence Of Bursts and Estimation Of Loss Cmentioning
confidence: 99%
“…Measurements in CHS have shown that in configurations with large toroidal viscosity, the damping of neutral beam induced toroidal flows can be described by neoclassical theory. 9 In configurations of the device where the toroidal viscosity is reduced, anomalous shear viscosity is necessary to explain the measured damping. A similar result was observed in Wendelstein-7 Advanced Stellarator ͑W7-AS͒.…”
Section: Introductionmentioning
confidence: 99%